Grécia e Roma no Universo de Augusto - Ana Maria César Pompeu (Classica Digitalia: Humanitas Supplementum - Estudos Monográficos, 2015)
This book encompasses papers presented at the XXVII Classical Studies Week (2014) of the Federal University of Ceará. The Symposium was consecrated to the bimillennial celebration of Augustus' death, and proposed discussions about cultural dialogues between Greece and Rome under Augustan ideology. How do rhetoric, philosophy, literature and history engage in such dialogues and in such controversial ideology? The papers in this book highlight aspects of that discussion, and are divided into three sections: Section I contemplates philosophy, rhetoric and politics, particularly in the relationship between young Octavian and Cicero; Section II contemplates Augustan literature (Horace, Virgil, Tibullus and Ovid); finally, Section III approaches history and Greek comedy through Plutarch.